Microencapsulated phase change material via Pickering emulsion based on xylan nanocrystal for thermoregulating application. (15th February 2023) - Lv, Ziwen; Rao, Jun; Lü, Baozhong; Chen, Gegu; Hao, Xiang; Guan, Ying; Bian, Jing; Peng, Feng
Abstract: Phase change materials (PCM) are promising for thermal regulation and energy storage, but suffer from the deformation and leakage of capsules. Herein, inspired by cellulose nanocrystal (CNC), xylan nanocrystal (XNC) with a dimension of 25–60 nm was successfully prepared through oxalic acid hydrolysis of high-crystalline xylan as raw materials via a top-down approach. With the introduction of hydrophobic groups, compared to XNC, succinylated XNC showed more remarkable emulsifying property over 7 days of storage at room temperature. Microencapsulated PCM composite consisting of sodium alginate (SA) as "matrix" and succinylated xylan nanocrystal (XNC) stabilized paraffin-based Pickering capsule (PCM beads) as "core" was facilely fabricated. PCM composite with the latent heat of 105.59 J·g −1 showed excellent thermoregulating performance. Our work suggests a new pathway toward sustainability of hemicelluloses in the application of food emulsion and thermal energy management. Graphical abstract: Unlabelled Image